THE EFFECTIVENESS OF THE ROLE OF GOVERNMENT INTERNAL SUPERVISORY APPLIANCES (APIP) IN THE INSPECTORATE OF NORTH SUMATRA PROVINCE - N Mahulae, Estina; Humaizi, Humaizi; Trimurni, Februari (RADJA PUBLIKA, 2022)
The purpose of this study is to analyze the effectiveness of the role of the Government Internal Supervisory Apparatus (APIP) and what factors hinder the effectiveness of the role of APIP in the Inspectorate of North Sumatra Province. The method that will be used in this research is a qualitative approach with descriptive research methods. Data Collection Techniques are Observation, Interview, and Documentation. Data analysis techniques Data reduction, data assessment, and drawing conclusions. The results of the study on the Effectiveness of the Role of Government Internal Supervisory Apparatus (APIP) in the Inspectorate of North Sumatra Province have not been effective, which can be seen from the activities of the organization which is the elaboration of policies as the direction of achieving goals and objectives that contribute to the achievement of organizational goals, especially government organizations. The activities of the Inspectorate of the Province of North Sumatra are essentially everything that the Inspectorate of the Province of North Sumatra must do in accordance with their duties and main functions, besides that the planned activity can be used as a standard for the success of the work unit and at the same time can be used as a performance indicator that can be achieved from time to time. . Factors that hinder the effectiveness of the role of the Government Internal Supervisory Apparatus (APIP) in the North Sumatra Provincial Inspectorate Inadequate quantity and quality of human resources, Lack of adequate budget, Lack of technical equipment and no special examination room, Still weak in standardization and narrow understanding of Inspectorate duties, there is still overlapping inspection,